Between Modernization and Tradition: How does Culture Shape Older Taiwanese Women’s Perceptions of Successful Aging? - Li-Kuang Chen (Adult Education Research Conference, 2007)
The purpose of this study was to understand how Taiwan’s culture context shapes the definitions of successful aging of older women. By interviewing 14 older Taiwanese women who aged over 60 and regularly volunteered for at least two years, the findings supported that successful aging was culturally constructed.